The Role of Emerging Technologies in Transforming Physics Education - Ataiy, Sayed Mohaidin; Karimi, Mazullah; Maftunzada, Sayed Abdul Latif (Stallion Journal for Multidisciplinary Associated Research Studies, 2026)
Emerging technologies, including virtual reality (VR) simulations, interactive coding environments, augmented reality (AR) visualizations, and adaptive learning platforms, hold immense potential to transform physics education. This study examines the impact of these cutting-edge technologies on teaching and learning in physics, drawing on research from various studies. VR simulations can enhance students' spatial reasoning and conceptual understanding, while interactive coding environments encourage computational thinking and hands-on learning. AR visualizations can improve spatial awareness and engagement, and adaptive platforms can personalize the educational experience to meet individual needs. The findings indicate that the use of VR, interactive coding, AR, and adaptive learning platforms leads to the creation of more dynamic, engaging, and personalized learning experiences. By embracing these advancements, educators can foster the next generation of physicists and STEM leaders, equipping them with the skills and knowledge required to thrive in an increasingly technology-driven world. The integration of these innovative technologies is crucial for preparing students for the challenges and opportunities of the future. This study highlights the transformative potential of emerging technologies in revolutionizing physics education and shaping the future of STEM learning.